On the Weak Solution of a Semilinear Boundary Value Problem without the Landesman-Lazer Condition - Sikiru Adigun Sanni (International Journal of Differential Equations)
We prove the existence of weak solution to a semilinear boundary value problem without the Landesman-Lazer condition.